(3UdGI SjO GdWGFaI GdUhajI GdLfjO GdHZOGOj GdTGaYjs - (3eLghds
(3ChdgG (B:s
(3Gddge Ud hSde CaVd hCLed hCced hCbHd hCXgQ hCWgQ hCHgi hCMSf hCHQ hCcQe hCYR hCYXe hCTQa hCYdi hCRci hCHQc hCdWa UdhGJcs
(3BNQgG (B:s
(3eUGQY Gdgehe hGdZehe hGdCMRGf hJHdZ HgG GdWGdH ZGjI eG WdH JeJs
(3aj BNQg OYGA ef jQjO Cf jQi GdfHj Udi Gddg Ydjg hSde aj efGeg haGFOI aj GdhYX hGdEQTGO aj hQbJjfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3GdJUha hGdBOGH GdTQYjIs